Hearing improvement after vestibular schwannoma surgery in the era of the hearing preservation rule - case report and literature review - Fik, Zdenek; Lazák, Jan; Hrubá, Silvie; Čada, Zdeněk; Zverrna, Eduard; Betka, Jan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2022)
OBJECTIVES: Hearing preservation after vestibular schwannoma (VS) surgery remains a surgical challenge. In some patients with preserved inner ear function, hearing improvement is achievable. As it is currently impossible to determine which patients will present this outcome, predictions must rely on previously published reports. Our case report describes a patient who experienced hearing improvement from an unuseful level to a useful one after vestibular schwannoma surgery. METHODS: Surgery was performed via suboccipital retrosigmoid approach. The patient underwent a basic audiovestibular protocol before and after the surgery - pure tone and speech audiometry, otoacoustic emissions, auditory brainstem responses, electronystagmography - together with a detailed questionnaire study. Usefulness of hearing was evaluated using the AAO-HNS guidelines, supplemented by a frequency of 4 kHz. RESULTS: Hearing was preserved and even improved from an unuseful level to a useful one. Based on the available literature, the most informative predictive factors for such a result seem to be: sudden sensorineural hearing loss prior to surgery, elicitable otoacoustic emissions and the origin from the superior vestibular nerve. CONCLUSION: There are a limited number of studies on this topic and it is still impossible to regularly improve hearing in properly selected patients. Furthermore, the importance of postoperative hearing quality compared to other symptoms and complications remains debatable.
Keywords: audiometrie čistými tóny; výsledek terapie; lidé; Treatment Outcome; Hearing; Neuroma, Acoustic; Audiometry, Pure-Tone; vestibulární schwannom; sluch; Retrospective Studies; Humans; retrospektivní studie